Interest Rate Pass-Through in Romania and Other Central European Economies - Tieman, Alexander (IMF Working Papers; Working Paper ;, 2004)
Interest rate pass-through from policy interest rates to market rates and inflation has been hypothesized to play a lesser role in Romania than in other Central European transition economies. This paper tests this hypothesis and concludes that it cannot be supported by the data. Hence pass-through in Romania is concluded to be in line with that in comparable economies in the region. Moreover, the interest rate pass-through has become more pronounced over time.